The evolution of capital structure and operating performance after leveraged buyouts: Evidence from U.S. corporate tax returns - Cohn, Jonathan B.; Mills, Lillian F.; Towery, Erin M. (Journal of Financial Economics, 2014)
This study uses corporate tax return data to examine the evolution of firms' financial structure and performance after leveraged buyouts (LBOs) for a comprehensive sample of 317 LBOs taking place between 1995 and 2007. We find little evidence of operating improvements subsequent to an LBO, although consistent with prior studies, we do observe operating improvements in the set of LBO firms that have public financial statements. We also find that firms do not reduce leverage after LBOs, even if they generate excess cash flow. Our results suggest that effecting a sustained change in capital structure is a conscious objective of the LBO structure.